(untitled) (Barre, Mass., 1996)
The Wings to Awakening constitute the Buddha's own list of his most important teachings. Toward the end of his life, hestated several times that as long as the teachinhs in this list were remembered and put into practice, his message would endure. Thus the Wings constitute, in the Buddha's eyes, the words and skills most worth mastering and passing along to others.
Keywords: Buddhism; Doctrines